Highly Active and Stable Pd−GaOx/Al2O3 Catalysts Derived from Intermetallic Pd5Ga3 Nanocrystals for Methane Combustion. Issue 24 (26th November 2018) - Hou, Zhiquan; Liu, Yuxi; Deng, Jiguang; Lu, Yue; Xie, Shaohua; Fang, Xiuzhong; Dai, Hongxing
Abstract: Catalytic combustion of methane is widely used in industrial and transportation activities. The commonly used Pd‐based catalysts, however, are easily deactivated under hydrothermal conditions. In this work, we adopted a novel strategy to prepare a GaO x ‐doped Pd/Al2 O3 catalyst via the oxidative transformation of intermetallic Pd5 Ga3 nanocrystals supported on γ ‐Al2 O3 . We observed a synergistic effect between palladium and gallium oxide via formation of a bi‐functional active Pd−O−Ga phase, resulting in a highly active and exceptionally stable catalyst that could markedly suppress the sintering of noble metals under harsh conditions (hydrothermal treatment at 750 °C). Moreover, the presence of a large amount of surface oxygen vacancies and the surface Pd−O−Ga phase could promote methane combustion over the catalysts. It is believed that such a novel dual‐metal catalyst is promising in practical applications for methane combustion. Abstract : Effective synergy : The Pd−GaO x /Al2 O3 catalysts are prepared via the oxidative transformation of intermetallic Pd5 Ga3 nanocrystals supported on Al2 O3 . A synergistic effect between palladium and gallium oxide via formation of a bi‐functional active Pd−O−Ga phase is observed, resulting in a highly active and exceptionally stable catalyst that can markedly suppress the sintering of noble metals under harsh conditions. Surface oxygen vacancies and the surface Pd−O−Ga phase are the catalytically active sites.